2023
DOI: 10.3390/ijerph20031763
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Qualities That Enhance Outdoor Play in Community Playgrounds from the Perspective of Children with and without Disabilities: A Scoping Review

Abstract: For children, playgrounds are important environments. However, children’s perspectives are often not acknowledged in playground provision, design, and evaluation. This scoping review aimed to summarize the users’ (children with and without disabilities) perspectives on environmental qualities that enhance their play experiences in community playgrounds. Published peer-reviewed studies were systematically searched in seven databases from disciplines of architecture, education, health, and social sciences; 2905 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 117 publications
0
1
0
Order By: Relevance
“…Today's children's quality of life will drive our global future (ARUP, 2017). The right to play is a fundamental right of children and is the basis of a healthy, prosperous and developed society (Morgenthaler et al, 2023). Meanwhile, children are increasingly isolated from nature, stuck in a virtual world and contacting fewer people daily.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today's children's quality of life will drive our global future (ARUP, 2017). The right to play is a fundamental right of children and is the basis of a healthy, prosperous and developed society (Morgenthaler et al, 2023). Meanwhile, children are increasingly isolated from nature, stuck in a virtual world and contacting fewer people daily.…”
Section: Discussionmentioning
confidence: 99%
“…We are responsible for assuring the next generations a sustainable future and a good present so they will become healthy and educated mature tomorrow. The words "play" and "children" are inseparable, and children's right to play is rightly recognised as one of the fundamental rights by the United Nations Convention on the Rights of the Child (UNCRC, 2013; Murnaghan, 2019; Morgenthaler et al, 2023). According to Article 31 of the UNCRC: "Children have the right to relax and play, and to join in a wide range of cultural, artistic and other recreational activities" (UNCRC, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As emphasized in the literature, it is critical that families with children who have disabilities be engaged in this process as key stakeholders in research and practice to ensure that inclusion is considered and integrated practically. For example, a recent scoping review by Morgenthaler and colleagues suggested that children were knowledgeable about the play value of their community playgrounds, and therefore, their perspectives need to be more closely considered in evaluation of these spaces (46). Not only is it critical to engage playground users in audits to gain insight about playground experiences of inclusion, but also to maximize use of these community spaces by ensuring children's preferences and needs are being met when adaptations are being considered (47).…”
Section: Features To Foster Inclusive Playmentioning
confidence: 99%